Egyptian Women’s Agriculture Contribution; Assessment of the Gender Gap for Sustainable Development - El Khorazaty, Noha (AUC Knowledge Fountain, 2021)
Women’s contribution to the agriculture sector in developing countries is undeniable, yet they do not have equal access to the resources and opportunities they need to be more productive. Sustainable development entails inclusive and effective management of natural resources, this entails gender equity in agriculture. Bridging the gender gap in agriculture far exceeds the benefits of the individual. According to the latest estimates bridging the yield gap in agricultural productivity could possibly decrease the numbers of undernourished people in the world by around 100 – 140 million people. Sustainable agriculture development and gender equity necessitate policy interventions targeting the gender gap in agriculture resources. However, within the Egyptian national context, not enough research has been dedicated to quantifying and analyzing the gender gap in agriculture in Egypt. This thesis seeks to statistically analyze gender inequalities that constrain women’s roles in agriculture and food production, and undermine their capacity to contribute to the food and nutrition security in Egypt. The contribution of women in agricultural production is conceptualized in to three separate, but complementary analytical objectives. Objective (A), reveals that the real impact of rural females’ subsistence agriculture labor on rural household food security exceeds that of rural males. Investigating rural females’ subsistence agriculture labor uncovers the actual contribution of Egyptian rural women to rural community sustainability and highlight their capacity for agricultural production. Objective (B) identifies the demographic and institutional differences between male and female agriculture labor. This objective provides evidence to the hypothesis that agriculture is becoming increasingly feminized within the Egyptian national context. Objective (C) estimates the yield gap between male-headed and female-headed households (as closest available proxy to agricultural autonomy), estimated by net earnings per unit generated from principal agricultural assets, namely corps cultivation and livestock. Additionally, the agriculture resources gap is examined based on the framework of agricultural resources suggested by the FAO (2011). Under this objective the data provides evidence to the efficiency of female-headed households in agricultural production despite their limited resources compared to male-headed households. Finally, the findings of the study will lead to recommending a set of essential principles to promote inclusivity and gender-equity in agricultural development programs in Egypt.